2006
DOI: 10.1111/j.1471-4159.2006.04165.x
|View full text |Cite
|
Sign up to set email alerts
|

The age‐related attenuation in long‐term potentiation is associated with microglial activation

Abstract: It is well established that inflammatory changes contribute to brain ageing, and an increased concentration of proinflammatory cytokine, interleukin-1b (IL-1b), has been reported in the aged brain associated with a deficit in long-term potentiation (LTP) in rat hippocampus. The precise age at which changes are initiated is unclear. In this study, we investigate parallel changes in markers of inflammation and LTP in 3-, 9-and 15-month-old rats. We report evidence of increased hippocampal concentrations of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
178
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(203 citation statements)
references
References 53 publications
21
178
1
Order By: Relevance
“…We examined the expression of markers of microglial activation in tissue prepared from aged and young rats; the data show that there is a significant age-related increase in MHCII mRNA and protein expression, confirming previous findings that indicated that microglial activation is characteristic of the aged brain (Griffin et al, 2006). This is accompanied by an age-related decrease in CD200, although CD200R was unchanged (data not shown).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…We examined the expression of markers of microglial activation in tissue prepared from aged and young rats; the data show that there is a significant age-related increase in MHCII mRNA and protein expression, confirming previous findings that indicated that microglial activation is characteristic of the aged brain (Griffin et al, 2006). This is accompanied by an age-related decrease in CD200, although CD200R was unchanged (data not shown).…”
Section: Discussionsupporting
confidence: 86%
“…Neuroinflammatory changes are also a feature of animal models of AD; thus, transgenic mice, which overexpress human amyloid precursor protein (Tg2576), exhibit inflammatory changes (and deposition of amyloid plaques) in middle to older age, and treatment with ibuprofen reduces both inflammation and plaque deposition (Lim et al, 2000). Similarly, age-related neuroinflammatory changes have been reported, characterized by an increased expression of pro-inflammatory cytokines interleukin-1␤ (IL-1␤), IL-18, and IL-6 (Ye and Johnson, 2001;Griffin et al, 2006) and a corresponding decline in the anti-inflammatory cytokine IL-4 Nolan et al, 2005). Indeed, the decline in IL-4 directly contributes to the increase in IL-1␤, the deficit in longterm potentiation (LTP), and increases in age and amyloid-␤ (A␤)-induced glial cell activation Lynch et al, 2007;Lyons et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…A chronic inflammatory response, identified by increases in ED1 + activated microglia, has been demonstrated repeatedly in the CNS of young animals months after irradiation (8,10,13,14). To date, however, experimental studies of radiation-induced inflammation, brain injury and cognitive dysfunction have been conducted almost exclusively in animals a few weeks to a few months old, young ages that do not reflect important neurobiological changes that occur with normal aging, such as decreased proliferation and neurogenesis (15)(16)(17)(18), increased microglial activation (19,20) and expression of pro-inflammatory cytokines (20)(21)(22). Experimental studies of stroke, traumatic brain injury, exogenous cytokine administration, and axotomy support the hypothesis that aging impacts the intensity and duration of brain inflammation and glial activation following challenges (23)(24)(25)(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…Neuronal excitotoxicity leading to neuronal death [34,35] Hyperphosphorylated tau Formation of neurofibrillary tangles [36,37] Inflammation Exacerbation of tau pathology [38] , induction of Aβ release from neurons [39] , attenuation of long-term potentiation [40] , retraction of synapses [41] Metal ion dyshomeostasis Promotion of Aβ aggregation [42,43] Mutations in genes for presenillin-1 and -2, and Increased Aβ levels, linked to Aβ accumulation [44][45][46] amyloid precursor protein; ApoE 4 allele genotype Neurosci Bull February 1, 2013, 29(1): 111-120 114 thologies leads to increased Aβ production [67] . This finding may well explain the sporadic AD which does not involve mutations of genes implicated in Aβ generation.…”
Section: Glutamate Increasesmentioning
confidence: 99%